Design and manufacturing of Welded Vacuum Testing (WVT) tool - Ariyanto, Ariyanto; Fitrah, Muhammad Aqdar; salu, Salma; Amaluddin, Muh Nurul Haq; Latif, Arman; Alwi, Rahmat; Halim, Halim (Jurnal Polimesin, 2024)
To ensure the quality of welded joints in the hull area, welding testing is very important and must be carried out. But unfortunately, currently the quality testing process of welded joints was still limited to penetrant tests and lime tests. The purpose of this study was to obtain a portable welding testing machine that was able to obtain fairly accurate test results on hull welding defects using a vacuum system. The research method is experimental by involving data collection through field experiments, testing is carried out with the resulting weld defect research subjects and the length of testing time on 1G and 3G position welding. The results of the study by compared tests among Welded Vacuum Testing (WVT) machines, Magnetic Particle tests (MP), and Penetrant Tests (PT). The three experiments detected leaking weld defects, spark sparks, pinholes, overlaps, and undercuts. For test results with machines made, welding defects that were successfully detected were leaks in the 1G position welding workpiece and undercut in the 3G position welding workpiece. Air bubbles at a vacuum pressure of 0.2 bar are detected, meaning that there is a defect in the welded joint. This tool can be used in bilge testing.